(untitled) (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2018)
ينطوي هذا البحث على حقل الألفاظ الدالة على القرابات والعلاقات الاجتماعية في لزوميات أبي العلاء المعري، وبصورة أكثر تحديداًً على جمع الألفاظ المتنوعة الواردة ضمن هذا المجال، وذكر العـدد الذي تكررت ضمنه كل لفظة على حـِدَه. وقـد قـُسِّم هـذا الحقل إلى مجموعات فرعية قد انطوت على الألفاظ الدالة على قرابة الدم من الذكـور مثل: جـد ـ عـم ـ خال ـ والـد ـ أخ ـ شقيـق ـ نجـل، ومن الإنـاث مثل: عمة ـ خالة ـ أم ـ شقيقة ـ بنت. هذا بالإضافة إلى الألفاظ الدالة على قرابة الزواج والمصاهرة من الذكور مثل: زوج ـ صهر ـ حمأ، ومن الإنـاث مثل: زوجـة ـ حمـاة ـ كنـة. كما انطوى هذا الحقل على العلاقات الاجتماعية التي تسود بين النـاس سواء الإيجابيـة منها القائمة على التآلف مثل: صديق ـ جـار ـ زائر، أو السلبية القائمة على التنافر والتعادي مثل: عـدو ـ خصم. وبعد الانتهاء من هذا الحقل تمَّت المقارنة ما بين تكرارات هذه الألفاظ وما انطوت عليه من دلالات متنوعـة، هذا بالإضافة إلى إظهار العلاقات الدلالية التي وُجـِدت ما بين هذه الألفـاظ، وذلك من ترادف وتضاد. وقد ارتأينا أن نُطبِّق نظرية الحقول الدلالية على ديوان اللزوميات لأبي العلاء المعري، نظراً لما يمكن أن يكون لنزعته التأملية العميقة فيما اختلف من جوانب الحياة والكون، ولتنوع ثقافاته وتباين اتجاهاتها من دور حيوي في إغناء لغته وتحفيز على البحث فيما اختلف من جوانبها هي الأخرى. This research underlies the field of words indicating the relations and social connections in the obligations of Abi Al Alaa Al Maarri, and more particularly the collection of the various words mentioned within this field, and the number within which each word being separately repeated was mentioned. This field is divided into branch groups including the words denoting the blood relationship, such as: grandfather ـ uncle on the father’s side ـ uncle on the mother’s side ـ father ـ brother ـ full brother ـ son and as for females: aunt on paternal side ـ aunt on maternal side ـ mother ـ sister and daughter. This in addition to the words indicating the matrimonial and in ـlaws relation, of males such as: husband ـ brother in law ـ father in law, and of the females such as: wife ـ mother in law on the husband’s side and daughter in law. This field include the social relations that prevail among people whether they be the positive ones based on familiarity such as: friend ـ neighbor ـ visitor, or the passive ones based on aversion and enmity, such as: enemy and opponent After finishing this field comparison is made between the repetition of these words and the various indications included in them. This in addition to giving prominence to the indicative relations that are found among these words, of these are synonyms and antonyms.